Assessing the Impact of Drought and Effective Management Strategies in Afghanistan - Mangal, Mohammad Rafiq; Aribzai, Abidullah; Safi, Lutfullah (Journal of Natural Sciences – Kabul University)
Drought is a recurring natural phenomenon that has severe consequences for the people of Afghanistan. Despite its frequent occurrence, no comprehensive strategies have been implemented to mitigate its effects, leaving communities highly vulnerable. This study examines drought management approaches in Afghanistan, utilizing both quantitative and qualitative research methods. Data were collected through structured interviews with 20 drought management specialists, using a purposeful sampling technique. The interviews consisted of five key questions designed to assess current management strategies and their effectiveness. The findings indicate that Afghanistan is among the countries most severely impacted by drought, with 2019 recording the highest number of affected individuals in the past 23 years. The research highlights the urgent need for proactive policies and community-driven initiatives to reduce the long-term effects of drought. By adopting effective drought management strategies, the government, policymakers, and local communities can enhance resilience and better safeguard themselves against future occurrences.